Long and Short of It: Early Response Predicts Longer‐Term Outcomes in Pediatric Weight Management. Issue 2 (24th January 2019) - Gross, Amy C.; Kaizer, Alexander M.; Kelly, Aaron S.; Rudser, Kyle D.; Ryder, Justin R.; Borzutzky, Claudia R.; Santos, Melissa; Tucker, Jared M.; Yee, Jennifer K.; Fox, Claudia K.; ,
Abstract : Objective: This study aimed to examine whether 1‐month BMI improvement is predictive of superior 6‐ and 12‐month BMI changes in a national sample of youth in pediatric weight management treatment. Methods: Participants were 4‐ to 18‐year‐olds from the Pediatric Obesity Weight Evaluation Registry, a prospective study collecting data from 31 pediatric weight management programs across the United States. Response at 1 month was defined as ≥ 3% BMI reduction; success at 6 and 12 months was defined as ≥ 5% BMI reduction from baseline. Analyses used linear and logistic regression with robust variance estimation. Results: Primary analyses were completed with 687 participants (mean age 12.2 years). One‐month responders demonstrated significant improvements in BMI compared with nonresponders at 6 months (BMI, −2.05 vs. 0.05; %BMI, −5.81 vs. 0.23; P  < 0.001 for all) and 12 months (BMI, −1.87 vs. 0.30; %BMI, −5.04 vs. 1.06; P  < 0.001 for all). The odds of success for 1‐month responders were 9.64 (95% CI: 5.85‐15.87; P  < 0.001) times that of nonresponders at 6 months and 5.24 (95% CI: 2.49‐11.02; P  < 0.001) times that of nonresponders at 12 months. Conclusions: In treatment‐seeking youth with obesity, early BMI reduction was significantly associated with greater long‐term BMI reduction. Nonresponders may benefit from early treatment redirection or intensification.